(untitled) (Global Journal of Human-Social Science, 2013)
At the heart of all these deep transformations is more increasing, almost defining role knowledge and information as play substrata of «information society». The mankind opened for itself and actively exploits a new resource-information. Information society puts forward on the arena new type of the power, at the heart of which activity-mastering by a new resource: information and knowledge.